Cooperative NHC and Photoredox Catalysis for the Synthesis of β‐Trifluoromethylated Alkyl Aryl Ketones - Meng, Qing‐Yuan (Angew Chem Int Ed Engl, 2020)
Despite the great potential of radical chemistry in organic synthesis, N‐heterocyclic carbene (NHC)‐catalyzed reactions involving radical intermediates are not well explored. This communication reports the three‐component coupling of aroyl fluorides, styrenes and the Langlois reagent (CF(3)SO(2)Na) to give various β‐trifluoromethylated alkyl aryl ketones with good functional group tolerance in moderate to high yields by cooperative photoredox/NHC catalysis. The alkene acyltrifluoromethylation proceeds via radical/radical cross coupling of ketyl radicals with benzylic C‐radicals. The ketyl radicals are generated via SET reduction of in situ formed acylazolium ions whereas the benzylic radicals derive from trifluoromethyl radical addition onto styrenes.